2003
DOI: 10.1074/jbc.m300874200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Yeast Cytosine Deaminase

Abstract: Yeast cytosine deaminase is an attractive candidate for anticancer gene therapy because it catalyzes the deamination of the prodrug 5-fluorocytosine to form 5-fluorouracil. We report here the crystal structure of the enzyme in complex with the inhibitor 2-hydroxypyrimidine at 1.6-Å resolution. The protein forms a tightly packed dimer with an extensive interface of 1450 Å 2 per monomer. The inhibitor was converted into a hydrated adduct as a transition-state analog. The essential zinc ion is ligated by the 4-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 27 publications
5
110
0
Order By: Relevance
“…3B). These data supported a model for CDA activity in which the active-site flap restricted substrate access to the active site as observed for ScCD (30). The observation that both the ScCDD1-EcL19-CDD1* and ScCDD1-AL-⌬(␣1)-CDD1* constructs deaminated cytidine in vitro demonstrated that the purified recombinant enzymes exhibited both folding and catalytic capabilities.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…3B). These data supported a model for CDA activity in which the active-site flap restricted substrate access to the active site as observed for ScCD (30). The observation that both the ScCDD1-EcL19-CDD1* and ScCDD1-AL-⌬(␣1)-CDD1* constructs deaminated cytidine in vitro demonstrated that the purified recombinant enzymes exhibited both folding and catalytic capabilities.…”
Section: Resultssupporting
confidence: 77%
“…The tertiary fold of the CDD1 monomer (Fig. 1B) exhibited high structural homology to the catalytic domains of known bacterial CDAs from E. coli and B. subtilis (29), as well as ScCD (30), despite modest sequence identity; respective rms deviation values from superpositions were 1.32 Å (28% identity), 0.95 Å (43%), and 1.42 Å (16%). The tertiary fold of the deaminase catalytic domain was a triangular ␤-sheet comprising five core strands flanked on either broad face by three ␣-helices (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations